Measurement of welding dilution from images using active contours - Pedro Pedrosa Rebouças Filho (2009)
Welding dilution is the chemical composition modification of the weld metal, caused by the portion of base metal that suffers melting and starts to form the fusion zone. Its measure is given by the percentage of the base metal that takes part in the formation of the weld filet, and it varies according to the used welding process, type of join, pre-heat temperature, consumable, parameters of welding, among others factors. In many applications, the dilution is determinative in the performance of the welded materials and, therefore, can be responsible by severe failures that may occur during in service. In hard facing welding it is desirable to decrease the dilution so that the chemical composition and the properties of the weld deposit are less influenced by the properties of the base metal, generally inferior when regarding the mechanical resistance. By the other hand, in the dissimilar welding the desired dilution can be maximum or minimum depending on the types of materials to be joined. In general, manual measurement of welding dilution is accomplished by relating the area of the base metal involved in the welding with the area of the welding metal. Beyond the traditional manual measurement method, commercial systems based on image analysis techniques can be used; however, these systems present some problems that often demand the user intervention. In this direction, the present work had as main objective the development and analyses of a computational system, based on the active contours methodology, capable to measure the value of the welding dilution from images. To validate the developed system, comparisons were accomplished between the results obtained in 20 samples by using it and a commercial system commonly used in the welding field. Based on the comparisons results, one can conclude that the measurement of welding dilution accomplished by the developed system is faster and more accurate, further than eliminating the subjective operators interpretation.